Evaluasi Prosedur Penjualan Tunai Pada PT. Pasoka Sumber Karya Di Padang - Putri, Irmanora Eka (Asosiasi Dosen Akuntansi Indonesia, 2022)
The use of effective sales procedures will help the development of the company in the long term. One of them is by using a flowchart on a cash sales system. The purpose of this study is to provide evaluation results of cash sales procedures for PT Pasoka Sumber Karya. The method used in this study is qualitative data analysis methods. The results obtained are that the cash sales procedure at PT Pasoka Sumber Karya has several stages, starting from receiving sales orders and receiving cash, shipping goods, administration, and accounting.